Control interno basado en coso i y su incidencia en la Productividad de las áreas operativas de la empresa hacienda Tabaganesha S.A. del cantón Buena Fe, año 2019 - Rivas Cedeño, María Isabel (2020)
The general objective of this research project is to evaluate the incidence of internal control based on COSO I in the management of productivity in the operating areas of the company Hacienda Tabaganesha S.A. As part of the research methodology used, applied, descriptive and biliographic research was used. Among the methods used, the descriptive, inductive and analytical method were mentioned, which allowed the extraction of important variables related to the research. Compliance indicators, COSO I internal control questionnaires and management indicators were used. The results of the investigation show that the company's assets are not being used to the maximum, purchases are not compensating for the optimal use of inputs, and employees are not being trained in their functions; In the operational areas of the company, the level of confidence obtained was 75%, the same that appears in the range of confidence level MODERATE while the level of risk obtained was 25%, the same that appears in the range of level LOW risk; Also, the management of the budget in the productivity of the company indicates that the use of the 2018 period is not optimal compared to the 2019 period, the projected is not being met and the production level is not being optimal. Keywords: Internal control evaluation, COSO 1 components, productivity of operational areas, agricultural inputs, tobacco leaves